The Study of the Relationship of Procalcitonin (PCT) Levels and C-Reactive Protein (CRP) Levels in Patients Diagnosed by a Doctor Who is Infected with COVID-19, Phra Nakhon Si Ayutthaya Hospital in 2021 - Wannacharoen, Ekkachai (Journal of Preventive Medicine Association of Thailand, 2023)
Objective: The Study of the relationship of procalcitonin (PCT) levels and C-reactive protein (CRP) levels and study of procalcitonin levels and C-reactive protein levels in pneumonia and nonpneumonia and secondary bacterial infection in COVID-19 case. Methods: This retrospective study of 383 COVID-19 patients was conducted in Phra Nakhon Si Ayutthaya hospital between 1st July and 30th November 2021. Patient background, clinical aboratory with focus on PCT and CRP level. Statistics using general data are number, maximum and minimum, percentage, mean, standard deviation. Studies on the relationship of Procalcitonin (PCT) levels and C-reactive protein (CRP) levels. Statistical compairsons were performed using Chi-Square Test, Fisher’s Exact and Independent t-test. A p-value<0.05 was considered statisfically significant. Results: Higher age and PCT levels were associated with patients infected with COVID-19 were statistically significant (p<0.05) and the mean of CRP of PCT< 0.25 ng/ml (58.09) was lower than PCT≥0.25 ng/ml (91.47) were statistically significant (p<0.05). COVID-19 patients presented with secondary bacterial infection in sputum culture 43 patients (11.2%) and blood culture 55 patients (14.4%). conclusion: Higher age and higher PCT levels were associated with patients infected with COVID-19 and low procalcitonin can reduce unnecessary CRP measurement and guiding the use of antibiotic therapy.